Effect of temperature and substrate on germination of the açoita-cavalo Luehea divaricata Mart. seeds (Revista de Ciências Agroveterinárias, 2013)
Luehea divaricata Mart (Tiliaceae) is a species with silvicultural potential widely used for reforestation of degraded areas. This study investigated the effect of temperature and substrate on the germination of açoita-cavalo seeds. The seeds were collected from three mast trees located in Entre Rios do Oeste, PR. Afterwards, they were cleaned, packed in kraft paper bags and stored for two months in a cold chamber with 85% RH and average temperature of 15°C. Seed germination was carried out in BOD using five temperatures (room, 20°C, 25°C, 30°C and alternating 20°C-30°C), and two substrates (paper and sand). The experimental design was completely randomized arranged in factorial 5x2 (substrate x temperatures) with four replications of 25 seeds. The data was submitted to ANOVA and the means compared by the Tukey test (p
Keywords: Luehea divaricata Mart.; Seed quality; Forest seed.